2016
DOI: 10.1680/jphmg.15.00019
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge modelling of tunnelling with forepoling

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link ABSTRACTGeotechnical centrifuge modelling provides a means by which geotechnical events and processes can be better understood. In particular, the technique has proved invaluable when investigating collapse mechanisms in small scale models that can be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…This is an obvious indication that the arrangements of forepoles may contribute to reinforce the soil around the excavation. A Pearson correlation analysis of measured and predicted values of Eur and Su, especially from the tests results performed by Divall et al (2016), showed a correlation of r = 0.6149, which indicates a moderate tendency for correlation. The lack of a strong correlation might be attributed to the fact that the soil was artificially improved by the addition of forepoles.…”
Section: Analysis Of Centrifuge Testsmentioning
confidence: 94%
“…This is an obvious indication that the arrangements of forepoles may contribute to reinforce the soil around the excavation. A Pearson correlation analysis of measured and predicted values of Eur and Su, especially from the tests results performed by Divall et al (2016), showed a correlation of r = 0.6149, which indicates a moderate tendency for correlation. The lack of a strong correlation might be attributed to the fact that the soil was artificially improved by the addition of forepoles.…”
Section: Analysis Of Centrifuge Testsmentioning
confidence: 94%
“…The centrifugal model test is a proven approach and has been widely applied in the field of geotechnical engineering testing. In the early stage, Schofield used a centrifuge to analyze geotechnical problems [17][18][19][20][21][22][23][24][25][26][27], then the centrifuge tests were gradually applied to all aspects of geotechnical engineering [18][19][20][21][22][23]. Also, the centrifuge was used for tunnel analysis [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the centrifuge was used for tunnel analysis [24][25][26]. The true stress conditions of a metro tunnel can be modeled by adjusting the centrifugal acceleration [27]. However, different collapsible conditions of the metro tunnel caused by foundation soaking cannot be well simulated in the currently CTE [21,[28][29][30][31] due to its inherent limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [18] analyzed the impacts of the pipe roofs on the deformation mechanism of the dry sand soil; the whole process of deformation development was studied in their research. Other authors [19][20][21] have studied the influence of design parameters on the performance of pipe roofs research. In their study, different aspects such as the installation angle, diameter and transverse spacing of pipe roofs were considered.…”
Section: Introductionmentioning
confidence: 99%